Community policing practice in the Nigerian police: Implications of employee burnout - Okoka, Happiness; Kheswa, Jabulani Gilford (Edelweiss Applied Science and Technology, 2024)
The Nigerian police force's implementation of community policing has coincided with increased criminal activities, exacerbated by factors like high youth unemployment, inadequate healthcare, malnutrition, poverty, banditry, and intercommunal conflicts. Against this backdrop, this aimed at assessing how burnout affects the implementation of community policing within the Nigerian police force. It specifically aimed to explore how three dimensions of burnout—emotional exhaustion, personal accomplishment, and depersonalization—influence officers' adherence to and practice of community policing principles. By examining these factors, the study sought to provide a comprehensive understanding of how the psychological well-being of police officers impacts their ability to effectively engage in community-oriented policing strategies. Participants were 369 police personnel, which consisted of 266 males and 94 females, with a mean age of 36.6 years. The study adopted the cross-sectional research design. The Maslach Burnout Inventory (MBI), and the Community Policing Inventory were used as measures of burnout and community policing respectively. Three hypotheses were tested with the multiple linear regression. Results revealed that emotional exhaustion did not significantly predict the practice of community policing (β = -.087, t = -1.332, p = .184), accounting for 8.7% variability in the practice of community policing. Personal accomplishment did not significantly predict the practice of community policing (β = .113, t = 1.951, p = .052), accounting for 11.3% variability in the practice of community policing. Depersonalization significantly negatively predicts the practice of community policing (β = -.275, t = -4.425, p <.001), accounting for 27.5% variability in the practice of community policing. It was recommended that future studies investigate the mediating and moderating variables that can provide a deeper understanding of the intricate relationship between burnout and community policing in the Nigerian setting.